2011
DOI: 10.21082/jhort.v21n4.2011.p372-384
|View full text |Cite
|
Sign up to set email alerts
|

Preferensi Konsumen terhadap Anggrek Phalaenopsis, Vanda, dan Dendrobium

Abstract: Penelitian preferensi konsumen dapat membantu pemulia dalam menentukan arah dan tujuan penelitian pemuliaan terkait dengan pemenuhan kebutuhan konsumen terhadap varietas unggul baru yang akan dihasilkan. Tujuan penelitian ialah untuk mengidentifikasi preferensi konsumen terhadap anggrek Phalaenopsis, Vanda, dan Dendrobium. Survei dilakukan terhadap 21 responden Phalaenopsis dan 32 responden Vanda, serta uji preferensi konsumen (100 panelis) anggrek Phalaenopsis, Vanda, dan Dendrobium dalam peragaan di arena Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
2
0
3
Order By: Relevance
“…The results of the data obtained that 47% of respondents bought orchids based on the shape of the flowers, 43% were influenced by the colour of the flowers, 35% bought the orchid based on price considerations, and 29% of orchid buyers have the intention to purchase based on the duration of flower in the bloom. These results are equal to the research of Nurmalinda et al (2011) which reported that a flower's colour and ideal shape are important considerations for consumers when purchasing flowers. In contrast, the research of Palma (2010) whose reports that price is the highest factor affecting purchasing decisions, representing 30.90% of the influence, followed by size (26.28%) and species (25.58%), while colour (17, 23%) is the least important attribute of orchids.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The results of the data obtained that 47% of respondents bought orchids based on the shape of the flowers, 43% were influenced by the colour of the flowers, 35% bought the orchid based on price considerations, and 29% of orchid buyers have the intention to purchase based on the duration of flower in the bloom. These results are equal to the research of Nurmalinda et al (2011) which reported that a flower's colour and ideal shape are important considerations for consumers when purchasing flowers. In contrast, the research of Palma (2010) whose reports that price is the highest factor affecting purchasing decisions, representing 30.90% of the influence, followed by size (26.28%) and species (25.58%), while colour (17, 23%) is the least important attribute of orchids.…”
Section: Resultssupporting
confidence: 66%
“…Moreover, Dendrobium is mostly used in many ceremonies and festivals. According to Nurmalinda et al (2011), Dendrobium, which has green coloured-flower, is preferred to other varieties. Additionally, consumers prefer Phalaenopsis, which has white flowers, because it radiates bright colours in terms of attractiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Maka dari itu, karena banyak tersedia bunga floral seperti janur dari kelapa dan juga gemitir, maka dapat menambah nilai ekonomis bagi bunga-bunga tersebut yang biasanya sehari-hari digunakan sebagai persembahan umat Hindu di Bali setiap hari. Industry tanaman hias merupakan usaha fashion plants, selera konsumen sangat menentukan tipe yang diinginkan pasar (Nurmalinda et al, 2011;Widyastoety & Santi, 2012). Apabila melihat kebutuhan industry pariwisata dan perhotelan maka rangkaian bunga dengan bahan material dari bunga segar local, seperti gemitir, kamboja, kembang ratna dan juga hydrangea, dapat membantu keberlangsungan ekonomi penduduk.…”
Section: Gambar 6 Guru Merangkai Menggunakan Bunga Lokalunclassified
“…Dendrobium merupakan salah satu jenis anggrek yang saat ini paling populer diperjualbelikan karena bentuk dan warna bunganya bervariasi. Bunga Dendrobium memiliki tangkai bunga tegak dengan jumlah kuntum bunga pertangkai 10-15 kuntum bunga, berwarna cerah dan waktu segar bunga (shelf life) mencapai 3-4 bulan (Nurmalinda et al, 2011).…”
Section: Pendahuluanunclassified